2001
DOI: 10.1086/320369
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Cold Neutral Interstellar Medium on 10–100 AU Scales

Abstract: We have used the Very Long Baseline Array (VLBA) and the Very Large Array (VLA) to image Galactic neutral hydrogen in absorption towards four compact extragalactic radio sources with 10 milliarcsecond resolution. Previous VLBA data by Faison et al (1998) have shown the existence of prominent structures in the direction of the extragalactic source 3C 138 with scale sizes of 10-20 AU with changes in HI optical depth in excess of 0.8 ± 0.1. In this paper we confirm the small scale H I optical depth variations tow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 21 publications
4
55
0
Order By: Relevance
“…However, around the Sun the mean free path length for neutral H is of the order of a few 100 AU, so that neutral gas variations should probably be at least on scales larger than these distances. Alternative interpretations of these phenomena that would not require the assumption of such small-scale spatial variations are also under debate (Faison & Goss 2001). At the measured relative velocity of 26.3 km s −1 the Sun traverses 25 AU in approximately 5 years, and thus potential variations in the parameters on that scale should become apparent on a time scale of 5 to 10 years, if they exist.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…However, around the Sun the mean free path length for neutral H is of the order of a few 100 AU, so that neutral gas variations should probably be at least on scales larger than these distances. Alternative interpretations of these phenomena that would not require the assumption of such small-scale spatial variations are also under debate (Faison & Goss 2001). At the measured relative velocity of 26.3 km s −1 the Sun traverses 25 AU in approximately 5 years, and thus potential variations in the parameters on that scale should become apparent on a time scale of 5 to 10 years, if they exist.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Thus, roughly speaking, if the average Mach number of the turbulence is 10, we may expect an increase of the limiting size for nearly adiabatic cooling to ∼0.01 pc. Over recent years, new findings from optical absorption lines (Meyer & Lauroesch 1999;Lauroesch, Meyer & Blades 2000;Andrews, Meyer & Lauroesch 2001) and 21-cm line absorption (Dieter, Welch & Romney 1976;Diamond et al 1989;Frail et al 1994;Davis, Diamond & Goss 1996;Faison et al 1998;Faison & Goss 2001) have shown unmistakable evidence that in almost any viewing direction the ISM exhibits large contrasts in density 3 over scales ranging from 2×10 −5 to 0.03 pc. These observations provide strong support for the pervasive character of small structures, a conclusion that is consistent with their being shaped by the action of turbulence.…”
Section: The Puzzle Of Cold H Imentioning
confidence: 99%
“…Since then a number of studies of small-scale structures in H i have been performed, by 21-cm absorption lines against pulsars with time variability (e.g., Clifton et al 1988;Frail et al 1994), sampling the gas on scales of tens to hundreds of AUs, or using interferometric observations with the Very Long Baseline Array (VLBA) (e.g., Faison & Goss 2001) finding optical depth variations on about the same scales. Optical spectra at high spectral resolution have been taken of stars in globular clusters, providing a grid of very close sightlines (angular scales of only few arcsec) to detect structure in interstellar gas on scales down to 0.01 pc.…”
Section: Introductionmentioning
confidence: 99%